Grebek (Gerakan Bersih Kali): Upaya Pemberdayaan Masyarakat Dalam Menjaga Kebersihan Sungai Di Rw 03 Dan 04 Kelurahan Kapas Madya Baru - Intan Puspitasari; Luluk Atun Aliyah; Annisa Nurul Mufida; Agnes Tresia Silalahi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
River pollution caused by household waste is one of the serious environmental problems in RW 03 and RW 04 of Kapas Madya Baru Subdistrict, Surabaya. Low public awareness and the lack of waste management facilities have caused the river to become shallow, dirty, and foul-smelling. The GREBEK (Gerakan Bersih Kali / River Cleaning Movement) program is a form of community empowerment-based service that involves local residents, neighborhood leaders, and subdistrict officials in river clean-up activities, household waste education, and the installation of educational signboards containing information on waste types and their decomposition times. This study uses a descriptive qualitative method with a participatory approach. The results show that active community participation has successfully increased environmental awareness, social solidarity, and behavioral changes in maintaining river cleanliness. This program demonstrates that simple interventions can have a sustainable positive impact when carried out through collaborative and empowerment-based approaches.